Relationship between age and vas appetite score among patients with post-tuberculosis lung disease at Persahabatan National Respiratory Referral Hospital, Jakarta - Mahardika, Linda; Nurwidya, Fariz; Singal, Anna Maurina (World Nutrition Journal, 2025)
Background: Post-tuberculosis lung disease (PTLD) is a form of progressive lung tissue damage following tuberculosis (TB) infection. In addition to clinical symptoms, patients with PTLD often experience nutritional problems. Appetite plays a crucial role in determining adequate nutrient intake, which can affect nutritional status, the recovery process, and overall quality of life. One factor that may influence appetite is age. Although age is known to affect appetite, the relationship between the two has not been studied, particularly in patients with PTLD at Persahabatan Hospital, National Respiratory Centre.